The aesthetics of naturalistic landscapes in civic spaces: a study of preference - Ulrich, Amanda (Kansas State University, 2010)
Naturalistic landscapes have increased in popularity, especially in the landscape architecture profession, due to the push for greener and more sustainable landscape designs in civic spaces. The increase in popularity and resulting use of naturalistic landscapes by landscape architects creates a need to understand users’ preferences for naturalistic landscapes. Users need to have moderate to high preference levels for the naturalistic landscape spaces in order for such spaces to be successful. This work identifies and explains civic spaces, characteristics of traditional landscape designs, characteristics and history of naturalistic landscapes, and characteristics and details of previous preference studies that focused on people’s preferences for natural areas. This study also identifies current preference levels and background characteristics of respondents, which are used to determine who does and does not prefer naturalistic landscapes in civic spaces and why. A survey questionnaire targeted toward users of naturalistic landscapes identified opinions, preferences, and statistical data relevant to this study. A total of sixty-one surveys were completed and collected from two separate survey sites. Survey results were used to determine: 1. Preference levels of the respondents. 2. Background characteristics and values of the respondents. 3. Correlations and patterns between respondents’ preference levels and their background characteristics. 4. Correlations and patterns between respondents’ preference levels and their values and opinions. 5. Differences between the results from the two survey sites. Survey results and analyses indicate that perceived safety is a major factor that influences preference levels. Background characteristics such as the level of formal education and the participation in classes and seminars that focus on topics relevant to naturalistic landscapes are also significant indicators of preference levels. Another of the indicators is the participation in outdoor activities of all sorts. Along with determining the indicators of preference levels, the survey results were used in the comparison of the results from the two survey locations.
Keywords: Naturalistic landscapes; Aesthetic Preference; Landscape Architecture (0390)